Carbon benefits from avoiding and repairing forest degradation - Putz, F.E.; Nasi, Robert (Center for International Forestry Research, 2009)
Stopping illegal timber harvesting and adopting reduced-impact logging in the tropics, together with wildfire suppression, could cost-effectively reduce carbon emissions and enhance carbon uptake. Carbon uptake in degraded forests could be enhanced by better postlogging forest management practices and active restoration. REDD+ goals related to forest degradation are more achievable than ever due in part to recent improvements in remote sensing techniques for monitoring logging and wildfires coupled with increasing availability of hand-held global positioning systems, especially if the synergy with ongoing forest certification is fully utilised.